2016
DOI: 10.1186/s13046-016-0402-3
|View full text |Cite|
|
Sign up to set email alerts
|

Heregulin-1ß and HER3 in hepatocellular carcinoma: status and regulation by insulin

Abstract: BackgroundThe heregulin-1ß/HER3-driven pathway is implicated in several epithelial malignancies and its blockade is currently undergoing clinical investigation. Paradoxically, the status and the regulation of this pathway is poorly known in hepatocellular carcinoma (HCC).MethodsUsing 85 HCC obtained after tumour resection, heregulin-1ß and HER3 expression was evaluated by real-time RT-PCR, ELISA and/or immunohistochemistry. Statistics were performed to analyze associations between gene expression and clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…In support of this, we detected the presence of ErbB2 mRNA in human neutrophils by RT-PCR (Figure 4A) and a 60kD protein (lower molecular weight ErbB family products are well-documented (Jackson et al, 2013; Guillaudeau et al, 2012; Siegel, 1999; Ward et al, 2013) which was upregulated by GMCSF and dbcAMP (Figure 4B). ErbB3 was also detected in human neutrophils by ELISA (Figure 4C), at levels similar to those observed in other tissues in literature (Buta et al, 2016). We found ErbB3 expression was not regulated by growth factors, which may in part be due to regulation being primarily at the post-translational level.…”
Section: Resultssupporting
confidence: 87%
“…In support of this, we detected the presence of ErbB2 mRNA in human neutrophils by RT-PCR (Figure 4A) and a 60kD protein (lower molecular weight ErbB family products are well-documented (Jackson et al, 2013; Guillaudeau et al, 2012; Siegel, 1999; Ward et al, 2013) which was upregulated by GMCSF and dbcAMP (Figure 4B). ErbB3 was also detected in human neutrophils by ELISA (Figure 4C), at levels similar to those observed in other tissues in literature (Buta et al, 2016). We found ErbB3 expression was not regulated by growth factors, which may in part be due to regulation being primarily at the post-translational level.…”
Section: Resultssupporting
confidence: 87%
“…Firstly, our study was performed on patients of Caucasian ethnicity chronically infected with HCV, while the study by Hsieh et al included Asian patients prevalently infected with hepatitis B virus; in fact, previous reports showed that etiology of chronic liver disease could affect the performance of HCC biomarkers [ 24 ]. In addition, this is in good agreement with the results of a recent study showing that HBV and HCV infections were associated with different ERBB3 mRNA expression in HCC cells [ 25 ]. Regarding ethnicity, several studies showed that ethnic differences may influence cancer biomarker levels as well as drug response and survival, possibly reflecting different genetic alterations and epigenetic changes involved in the regulation of oncogenic pathways [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…GPC3 promotes cancerogenesis via activation of the Wnt/β-catenin signaling pathway and, hence, presents itself as a potential therapeutic target (Kolluri and Ho, 2019; Shih et al, 2020). Finally, another noteworthy receptor from the list is ERBB3 (HERT3) which is upregulated in chronic hepatitis B (CHB) but not hepatitis C induced HCC (Buta et al, 2016) corresponding to the liquid biopsy liver cancer sample composition we employed (>60% CHB) (Chen et al, 2022).…”
Section: Resultsmentioning
confidence: 99%